1974
DOI: 10.1037/h0036699
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual memory for numerousness in "nonpsychotic schizophrenics."

Abstract: Conducted an exploratory study on the assumption that a population of nonpsychotic schizophrenics could be identified by the Minnesota Multiphasic Personality Inventory (MMPI) 2-7-8 code and that these schizophrenics would exhibit the memory deficiencies associated with a thought disorder. 23 elevated MMPI 2-7-8 code and 23 nonelevated code Ss participated in a delayed paired-comparison task. Ss judged whether the 2nd of a pair of dot patterns consisted of "more" or "less" dots than the 1st, and the signal det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Fine (1973) interviewed college students with a 2-7-8 profile and formed a clinical impression that half of them were nonpsychotic schizophrenics, although he did not have that impression of college students who scored in the normal range on the MMPI. Koh and Peterson (1974), Schulman (1976), andSterenko andWoods (1978) found various cognitive abnormalities in college students with 2-7-8 profiles.…”
Section: Earlier Attempts To Measure Personality Traits Of the Psycho...mentioning
confidence: 99%
“…Fine (1973) interviewed college students with a 2-7-8 profile and formed a clinical impression that half of them were nonpsychotic schizophrenics, although he did not have that impression of college students who scored in the normal range on the MMPI. Koh and Peterson (1974), Schulman (1976), andSterenko andWoods (1978) found various cognitive abnormalities in college students with 2-7-8 profiles.…”
Section: Earlier Attempts To Measure Personality Traits Of the Psycho...mentioning
confidence: 99%
“…Kelley and King (1979) examined the clinical records of college students with this pro-file and confirmed that the males (but not the females) appeared to be latent schizophrenics. Koh and Peterson (1974) and Schulman (1976) have found schizophreniclike cognitive deviancies in college students with 2-7-8 profiles.…”
Section: Eight Measures Of Psychosis Pronenessmentioning
confidence: 99%
“…Similarly, Kelley and King (1979) found that male college students with 2-7-8 profiles who were seen at a university mental health clinic received diagnoses of latent schizophrenia; the female students with this profile, however, received diagnoses within the neurotic spectrum. Through the use of nonclinical populations, Koh and Peterson (1974), Schulman (1976), and Steronko and Woods (1978) found that college students with 2-7-8 profiles showed cognitive deficits on tachistoscopic tasks similar to those seen in schizophrenics. Fine (1973) interviewed college students with 2-7-8 profiles and judged half of these subjects to be "well-functioning nonpsychotic schizophrenics."…”
mentioning
confidence: 99%
“…Several studies indicate that the MMPI 2-7-8 profile may also identify subjects at risk for psychosis. Through the use of hospitalized psychiatric samples, several researchers have found that this profile is commonly associated with a diagnosis of pseudoneurotic schizoprenia or of latent schizophrenia (Gilberstadt & Duker, 1965;Koh, Kayton, & Berry, 1973;Koh & Peterson, 1974;Peterson, 1963). Similarly, Kelley and King (1979) found that male college students with 2-7-8 profiles who were seen at a university mental health clinic received diagnoses of latent schizophrenia; the female students with this profile, however, received diagnoses within the neurotic spectrum.…”
mentioning
confidence: 99%